Properties of urea-formaldehyde particleboard from particles of mixed timber species / Jamaludin Kasim, Ahmad Fauzi Othman and Shaikh Abdul Karim Yamani - Kasim, Jamaludin; Othman, Ahmad Fauzi; Yamani, Shaikh Abdul Karim (Universiti Teknologi MARA Cawangan Pahang, 2005)
Mixed hardwood particles were used in the manufacture of urea-formaldehyde particleboard. Three different resin contents (8, 10 and 12%) and 1% wax content were used in the study. The target density was 700 kgm-3 . Increasing resin content resulted in an increase in the mechanical and dimensional properties of the particleboard. Wax addition improved the dimensional stability of the particleboard. However, all particleboards failed in their. thickness swelling exceeding the 8% benchmark as stipulated in the British standards.